Mitochondrial depletion syndrome type 3: the Lebanese variant - Majdalani, Marianne; Yazbeck, Nadine; El Harake, Lamis; Samaha, Jinane; Karam, Pascale E. (Frontiers in Genetics, 2023)
Introduction: Mitochondrial DNA depletion syndrome type 3 is an emerging disorder linked to variants in the deoxyguanosine kinase gene, which encodes for mitochondrial maintenance. This autosomal recessive disorder is frequent in the Middle East and North Africa. Diagnosis is often delayed due to the non-specificity of clinical presentation with cerebro-hepatic deterioration. The only therapeutic option is liver transplantation, although the value of this remains debatable. Methods: We describe the clinical, biochemical, and molecular profiles of Lebanese patients with this rare disorder. We also present a review of all cases from the Middle East and North Africa. Results: All Lebanese patients share a unique mutation, unreported in other populations. Almost half of patients worldwide originate from the Middle East and North Africa, with cases reported from only 7 of the 21 countries in this region. Clinical presentation is heterogeneous, with early-onset neurological and hepatic signs. Liver failure and lactic acidosis are constants. Several variants can be identified in each population; a unique c.235C>T p. (Gln79*) pathogenic variant is found in Lebanese patients. Outcome is poor, with death before 1 year of age. Conclusion: The pathogenic nonsense variant c.235C>T p. (Gln79*) in the deoxyguanosine kinase gene may be considered a founder mutation in Lebanon. Further genotypic delineation of this devastating disorder in populations with high consanguinity rates is needed.